PENGARUH NEGOSIASI TINGKAT MARGIN TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN PRODUK MURABAHAH DI BMT MIFTAHUSSALAM CIAMIS - Saepudin, Asep; Jaelani, Ihrom (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2025)
This study aims to determine the effect of negotiating the margin rate on customer decisions using murabahah products. The population in this study were 131 Murabahah customers at BMT Miftahussalam Ciamis, sampling using the Slovin formula with random sampling techniques. The sample used was 99 respondents. The data collection instrument used a questionnaire of 20 statement items with a Likert scale of 1-5 and tested for validity and reliability. Data analysis using simple linear regression with the help of SPSS V.25. Based on simple linear regression analysis at a significance level of 5%, the results of the partial test (t test) show that the calculated t value of 2.400 shows that it is greater than the t table (2.400> 1.984) and a significance value of 0.018 <0.05 so it can be concluded that H0 is rejected and Ha is accepted, which means that the negotiation of the margin rate has a positive and significant effect on the Customer's Decision to use Murabahah Products at BMT Miftahussalam Ciamis.